Fluid Behavior in Nanoporous Silica - Ok, Salim; Hwang, Bohyun; Liu, Tingting; Welch, Susan; Sheets, Julia M.; Cole, David R.; Liu, Kao-Hsiang; Mou, Chung-Yuan (Frontiers in Chemistry, 2020)
We investigate dynamics of water (H2O) and methanol (CH3OH and CH3OD) inside mesoporous silica materials with pore diameters of 4.0 nm, 2.5 nm, and 1.5 nm using low-field (LF) nuclear magnetic resonance (NMR) relaxometry. Experiments were conducted to test the effects of pore size, pore volume, type of fluid, fluid/solid ratio, and temperature on fluid dynamics. Longitudinal relaxation times (T1) and transverse relaxation times (T2) were obtained for the above systems. We observe an increasing deviation in confined fluid behavior compared to that of bulk fluid with decreasing fluid-to-solid ratio. Our results show that the surface area-to-volume ratio is a critical parameter compared to pore diameter in the relaxation dynamics of confined water. An increase in temperature for the range between 25oC and 50oC studied did not influence T2 times of confined water significantly. However, when the temperature was increased, T1 times of water confined in both silica-2.5 nm and silica-1.5 nm increased, while those of water in silica-4.0 nm did not change. Reductions in both T1 and T2 values as a function of fluid-to-solid ratio were independent of confined fluid species studied here. The parameter T1/T2 indicates that H2O interacts more strongly with the pore walls of silica-4.0 nm than CH3OH and CH3OD.